2017
DOI: 10.1007/s10862-017-9631-9
|View full text |Cite
|
Sign up to set email alerts
|

Sluggish Cognitive Tempo Symptoms Contribute to Heterogeneity in Adult Attention-Deficit Hyperactivity Disorder

Abstract: Attention-deficit hyperactivity disorder (ADHD) persists into adulthood in over 50% of cases, although its associated symptom profiles, comorbid problems, and neuropsychological deficits change substantially across development. Sluggish cognitive tempo (SCT) symptoms may contribute to associations between ADHD and comorbid problems and may partially explain the substantial heterogeneity observed in its correlates. 349 adults aged 18–38 years (M = 23.2, SD = 4.5, 54.7% male, 61.03% with ADHD) completed a multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 106 publications
(137 reference statements)
7
21
1
Order By: Relevance
“…This result is consistent with the findings related to hypothesis 2 that there is a significant correlation (0.63) between SCT and ADHD, and a significant correlation (0.25) can be found between self-esteem and ADHD. It is also consistent with the findings that mediation follow-up analyses revealed that SCT may at least partially explain the heterogeneity in ADHD (Kamradt Momany, and Nikolas, 2018). The higher levels of SCT also predicted higher levels of anxiety, depression, academic, and social weakness (Bernad, Servera, Becker, and Burns, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…This result is consistent with the findings related to hypothesis 2 that there is a significant correlation (0.63) between SCT and ADHD, and a significant correlation (0.25) can be found between self-esteem and ADHD. It is also consistent with the findings that mediation follow-up analyses revealed that SCT may at least partially explain the heterogeneity in ADHD (Kamradt Momany, and Nikolas, 2018). The higher levels of SCT also predicted higher levels of anxiety, depression, academic, and social weakness (Bernad, Servera, Becker, and Burns, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Further, given not only small effects, but also the nonsignificant moderation for positive emotional climate on the association of SCT to ADHD‐IN, several other nonfamilial (e.g., peers relationships) or nonenvironmental factors (e.g., biology) might be considered in future research examining potential moderating influences on the relations of SCT with ADHD‐IN and depression. Finally, we assumed that stronger associations of SCT with depression and ADHD‐IN would worsen impairment given preliminary research showing that adults with ADHD combined with SCT symptoms have more impairment compared to adults with fewer SCT symptoms (Kamradt et al, ). Although beyond the scope of the present paper, testing the three‐way interaction of family environment, SCT, and co‐occurring symptomatology as predictors of specific domains of functional impairment would be a needed and exciting next step.…”
Section: Discussionmentioning
confidence: 99%
“…SCT symptoms are also strongly related to, yet empirically distinct from, depression in adults (Becker, Burns, et al, 2017). In fact, some studies find stronger associations between SCT and internalizing symptoms (particularly depression) than between SCT and ADHD‐IN and internalizing symptoms (Becker, Langberg, et al, 2014; Kamradt, Momany, & Nikolas, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been shown that SCT is not best included as part of a general disruptive behavior factor (Lee et al, 2016). Rather, SCT is more strongly associated with internalizing symptoms than with externalizing behaviors (Becker et al, 2016), and SCT symptoms are associated with increased anxiety/depressive symptoms in adults (Becker, Burns, et al, 2018; Becker, Langberg, et al, 2014; Kamradt et al, 2017; Leikauf & Solanto, 2017; Wood, Lewandowski, et al, 2017). Studies of adults, primarily conducted in college students, have also found SCT symptoms to be associated with increased social withdrawal/isolation and loneliness, lower self-esteem, greater emotion dysregulation, suicide risk, and poorer sleep quality (Barkley, 2012; Becker, Burns, et al, 2018; Becker, Holdaway, et al, 2018; Becker, Luebbe, et al, 2014; Flannery, Becker, et al, 2016; Jarrett et al, 2017).…”
Section: Introductionmentioning
confidence: 99%